Screening potential of three maize topcross testers - Duarte, Iran de Azevedo; Ferreira, Josué Maldonado; Nuss, Cláudio Natalino (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to assess the potential of three elite inbred testers to evaluate and rank fifteen genetic materials for hybrid synthesis. Forty-five hybrids and four controls were evaluated in five different environments in the 2000/2001 growing season using a randomized complete block design with three replications. The main agronomic traits were assessed, including the corrected grain yield and plant and ear height. Estimates of general and specific combining ability were obtained using Griffing's method adapted by Vencovsky and Barriga. The average yield in the five environments ranged from 8.97 ton ha-1 to 12.21 ton ha-1. Twenty seven treatments outperformed the mean yield of the best control. The analysis of variance over environments revealed significant main effects of environments, general combining ability of the parents and testers, specific combining ability and significant interactions, such as environment x general combining ability of parents and also environment x general combining ability of testers. The testers allowed ranking and screening of the assessed genetic basis, suggesting as best combinations the crosses that included the HS1, HS2, HS5 and HT4 parents with the LF tester and the L10 and HS5 parents with the L05 tester.